2018
DOI: 10.15252/embr.201846756
|View full text |Cite
|
Sign up to set email alerts
|

Do not poison thyself

Abstract: The mechanisms by which poisonous plants and animals protect themselves against their own toxins provide interesting leads for synthetic biology with potential applications in medicine and agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Organisms are thought to cope with toxin exposure through diverse strategies that include target protein resistance mutations, toxin sequestration, and toxin removal ( 10 , 11 ). Frogs are resistant to STX ( 14 , 15 ), and Sxph may contribute to this property ( 16 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms are thought to cope with toxin exposure through diverse strategies that include target protein resistance mutations, toxin sequestration, and toxin removal ( 10 , 11 ). Frogs are resistant to STX ( 14 , 15 ), and Sxph may contribute to this property ( 16 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nature uses diverse strategies to counter toxin exposure that include target protein resistance mutations, toxin sequestration, and toxin removal ( 10 , 11 ). Although the best understood toxin resistance strategies involve target protein mutations ( 10 , 12 , 13 ), frogs display unusual resistance to STX poisoning ( 14 , 15 ) that is not believed to involve altered responses of frog Na V s to STX ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…This lipophilic, steroidal neurotoxin is thought to bind in the Na V inner pore ( Wang and Wang, 2003 ). How vertebrates that bear BTX or other small-molecule toxins avoid autointoxication remains unresolved ( Arbuckle et al, 2017 ; Almabruk et al, 2018 ; Hunter, 2018 ). Toxin-resistant mutants of target ion channels in host organisms ( Tarvin et al, 2017 ; Bricelj et al, 2005 ; Hanifin and Gilly, 2015 ; Jost et al, 2008 ) or their predators ( Geffeney et al, 2002 ; Geffeney et al, 2005 ; McGlothlin et al, 2016 ) have been suggested as the primary drivers of toxin resistance ( Santos et al, 2016 ), an idea supported by examples of tetrodotoxin (TTX)-resistant ( Hanifin and Gilly, 2015 ; Jost et al, 2008 ; Geffeney et al, 2002 ; Geffeney et al, 2005 ; McGlothlin et al, 2016 ) and saxitoxin (STX)-resistant ( Bricelj et al, 2005 ) Na V s, as well as epibatidine-resistant nicotinic acetylcholine receptors ( Tarvin et al, 2017 ) found in toxin-carrying metazoans.…”
Section: Introductionmentioning
confidence: 99%